Extensions of the Banach contraction principle in multiplicative metric spaces - е-Rome, Badshah; Sarwar, Muhammad (Vojnotehnički glasnik / Military Technical Courier, 2017)
In this paper, we have proven several generalizations of the Banach contraction principle for multiplicative metric spaces. We have also derived the Cantor intersection theorem in the setup of multiplicative metric spaces. Non-trivial supporting examples are also given.
Keywords: Multiplicative metric; Multiplicative open ball; Multiplicative Cauchy sequence; Multiplicative contraction